Phonics teacher's book : Teaching Jolly phonics with phonics pupil books 1, 2 and 3. - Wernham, Sara.; Lloyd, Sue.; Van-Pottelsberghe, Louise (UK : Jolly Learning Ltd., 2010)
This accompanies books 1, 2 & 3. It provides daily guidance for each of the corresponding pages in Pupil Books 1, 2 & 3.
Keywords: Reading -- Study and teaching (Primary) -- Phonetic method; English language -- Grammar -- Study and teaching (Elementary); English language -- Orthography and spelling -- Study and teaching (Elementary)